HLA-G1-expressing antigen-presenting cells induce immunosuppressive CD4(+) T cells - LeMaoult, Joël (National Academy of Sciences, 2004)
We recently reported that HLA-G1-transfected antigen-presenting cells (HLA-G1(+) APCs) were capable of inhibiting alloproliferative responses. The aim of the present work was to further study the function and the mechanisms of action of HLA-G1(+) APCs. We show here that HLA-G1(+) APCs are immunoinhibitory cells that (i) inhibit the proliferation of CD4(+) T cells, (ii) shed HLA-G1 molecules that might provide extra, non-antigen-specific, inhibitory or proapoptotic signals, (iii) induce CD4(+) T cell anergy, or at least long-term unresponsiveness, and (iv) cause the differentiation of CD4(+) T cells into suppressive cells. Thus, HLA-G(+) APCs might (i) be involved in the direct suppression of immune responses and (ii) contribute to long-term efficient immune escape or tolerance.